2019
DOI: 10.1093/eurpub/ckz186.141
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetics and pregnancy: perception of health risk by health professionals and pregnant women

Abstract: Contex During pregnancy, the International Federation of Gyneco-Obstetrics (FIGO) advocates limiting exposure to chemicals present in everyday products, including cosmetics. However, both pregnant women (PW) and perinatal health professionals (PHP) know still poorly this source of exposure. AIMS: The PERICOS-Quali Study aims to identify the perception of the risk associated with the use of cosmetics during pregnancy by PHP and PW. Methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Regarding safety in personal and household products, participants opted for less harmful options such as baby or natural products and discontinued using unnecessary items like hair dyes. This aligns with findings from another study where women used organic products, moisturizers, or anti-stretch marks during pregnancy while refraining from using perfumes and deodorants (Sauvant-Rochat et al, 2019 ). Moreover, participants in our study reported ceasing the use of hair dyes (73%), insecticide sprays (72%), mosquito repellents (60%), and home renovation products (59%) (Teysseire et al, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
“…Regarding safety in personal and household products, participants opted for less harmful options such as baby or natural products and discontinued using unnecessary items like hair dyes. This aligns with findings from another study where women used organic products, moisturizers, or anti-stretch marks during pregnancy while refraining from using perfumes and deodorants (Sauvant-Rochat et al, 2019 ). Moreover, participants in our study reported ceasing the use of hair dyes (73%), insecticide sprays (72%), mosquito repellents (60%), and home renovation products (59%) (Teysseire et al, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
“…In order to ensure the quality and supervision of cosmetics, China has successively promulgated relevant laws and regulations on cosmetics, which have become important measurement standards [7,8]. On the other hand, as far as the cosmetics market is concerned, the cosmetics industry is booming, creating a large number of jobs and also bringing great tax revenue to the country, and it has also been favored by related capital [9,10].…”
Section: Introductionmentioning
confidence: 99%